Laparoscopic Nephroureterectomy for Adult Patient with Primary Obstructive Megaureter - Kimito Osaka; Kazuhide Makiyama; Shinji Ohtake; Hiroyuki Yamanaka; Futoshi Sano; Noboru Nakaigawa; Yoshinobu Kubota (Case Reports in Urology)
A 29-year-old female with a complaint of abdominal distension was referred to our hospital. She had a history of being treated for pyelonephritis three times. By computed tomography and retrograde pyelography, she was diagnosed with adult left primary megaureter. Her left renal function was severely deteriorated. She hoped for surgical intervention before becoming pregnant. Laparoscopic nephroureterectomy for megaureters seems to be difficult due to the large size. By sucking urine from an inserted ureteral catheter and setting trocar positions, we successfully performed laparoscopic nephroureterectomy for megaureter.